The Role of Management as a User of Accounting Information: Implications for Standard Setting - Brigitte Eierle; Wolfgang Schultze (Journal of Accounting and Management Information Systems (JAMIS), 2013)
The aim of this paper is to analyze the question of whether the sole focus of standard setters developing accounting standards that are useful to external users for making decisions about providing resources to the entity result in useful accounting information. To answer this question, we analyzed the relationship between the stewardship function of financial accounting and the demand for information useful in making economic decisions on resource allocation (decision-making demand; decision-useful information) by external investors. We first analyse information within an efficiency-based framework of financial economics abstracting from agency conflicts. We demonstrate that decisions on resource allocation not only require forward-looking, but also backward-looking performance measures which indicate the necessity as well as the direction of corrective action. Next, we introduce information asymmetries and incentive problems. In this setting, the stewardship function of accounting gains relevance. External users now need not only information for their investment decisions but also information to use in assessing management performance and to gain insight into how management used the entity's resources. Since however, managers anticipate the way they are evaluated, any accounting information used to control management has an incentive effect and alters management's internal decision-making. Therefore, standard setters cannot ignore the incentive effect (stewardship function) of financial accounting information and the consequence it has for decision-making. If standard setters consider decision-usefulness and stewardship as compatible functions of accounting, accounting rules need to serve both functions simultaneously, that is, provide information that is useful for investors for making economic decisions and at the same time provide incentives for managers to act in the owners' best interests. Or, if in fact the two functions are considered distinct and incompatible, then they must be separated and considered explicitly. That is, managers should then not be held accountable for their actions based on accounting information.
Keywords: G14; M41; M44; M45; D82; 650; Decision-Usefulness; Qualitative Characteristics; Stewardship; Standard Setting